Flood Prognosis of Keyang Sub-Sub Watershed Using SIMODAS for Strategic Environmental Assessment on Spatial Planning of Ponorogo District - Haji, Alexander Tunggul Sutan; Wirosoedarmo, Ruslan; Syiama, Lissa Rullis (Jurnal Teknologi Pertanian, 2012)
The research aimed to apply SIMODAS in order to predict the flood hydrograph in Keyang sub-sub watershed used for Strategic Environmental Assessment was instrument used for urban planning at Ponorogo district. The method used is data analysis. The data requirement covers spatial and atribut data. The spatial data were digital map of topography, river network, soil types and land use. The land use digital map covers the map of existing condition and the map of spatial planning Ponorogo district. While, the atribute data were daily rainfall. The simulation by using SIMODAS aimed to compare the existed flood hydrograph curve and the change of flood hydrograph curve caused by the change of landuse. The expected benefit is that it can help predict the flood hydrograph, so the government of Ponorogo be more leverage to prevent floods. The result showed that the flood hydrograph of existing condition for the 10, 25, and 50 year repeated period describe the flood peak discharge 1672.94 m3/second, 2030.876 m3/second, and 2255.146 m3/second. While, the at time needed to reach the flood peak discharge were 101 minutes, 99 minutes, and 98 minutes. The change of land use can cause the flood peak discharge becomes 1727.457 m3/second, 2085.384 m3/second, and 2317.951 m3/second for the 10, 25, and 50 year repeated period. This also cause the flood peak time to become 99 minutes, 96 minutes, and 93 minutes. Keywords: flood hydrograph, SIMODAS, environmental assessment, ponorogo